Weibull Distribution Function for Wind Energy Estimation of Gharo (Sindh) - Muhammad Shoaib; Imran Siddiqui; Firoz Ahmed; Saif ur Rehman; Muhammad Rashid Tanveer; Saif Uddin Jilani (Journal of Basic & Applied Sciences, 2015)
Weibull distribution function is fitted to a measured wind speed data set at mast height of 30 m and Gharo-Sindh (Pakistan) is selected as a case site under study. Wind speed data recorded in one minute interval for the year 2004 is used to estimate Weibull parameters (k and c). Weibull parameters are calculated using Modified Maximum Likelihood Method (MMLM), Maximum likelihood Method (MLM) and Method of Moment (MoM) and the results obtained are compared. Kolomogorov-Smirnov test, Root Mean Square Error (RMSE) and R2 tests are performed to test the goodness-of-fit of the Weibull distribution function. The analysis is based on recorded monthly and yearly wind speed data. Goodness-of-fit tests indicate a better performance of MMLM and MLM as compared to MoM. Wind power density is estimated for the site under study using MMLM and Weibull function estimator. A lowest Weibull mean wind speed of 3.73 m/s in the month of October and highest value of 7.90 m/s for August are observed and correspondingly power densities of 80.95 W/m2 and 425.87 W/m2 are obtained. Descriptive statistics for the measured wind speed data is also evaluated.